Multirotor UAV icing correlated to liquid water content measurements in natural supercooled clouds - Anna J. Miller; Christopher Fuchs; Nadja Omanovic; Fabiola Ramelli; Patric Seifert; Robert Spirig; Huiying Zhang; Emilie Fons; Ulrike Lohmann; Jan Henneberger (Cold Regions Science and Technology, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Comprehensive ECG reference intervals in C57BL/6N substrains provide a generalizable guide for cardiac electrophysiology studies in mice - Manuela A. Oestereicher; Janine M. Wotton; Shinya Ayabe; Ghina Bou About; Tsz Kwan Cheng; Jae-Hoon Choi; Dave Clary; Emily M. Dew; Lahcen Elfertak; Alain Guimond; Hamed Haseli Mashhadi; Jason D. Heaney; et al. (Mammalian Genome, 2023)
Reference ranges provide a powerful tool for diagnostic decision-making in clinical medicine and are enormously valuable for understanding normality in pre-clinical scientific research that uses in vivo models. As yet, there are no published reference ranges for electrocardiography (ECG) in the laboratory mouse. The first mouse-specific reference ranges for the assessment of electrical conduction are reported herein generated from an ECG dataset of unprecedented scale. International Mouse Phenotyping Consortium data from over 26,000 conscious or anesthetized C57BL/6N wildtype control mice were stratified by sex and age to develop robust ECG reference ranges. Interesting findings include that heart rate and key elements from the ECG waveform (RR-, PR-, ST-, QT-interval, QT corrected, and QRS complex) demonstrate minimal sexual dimorphism. As expected, anesthesia induces a decrease in heart rate and was shown for both inhalation (isoflurane) and injectable (tribromoethanol) anesthesia. In the absence of pharmacological, environmental, or genetic challenges, we did not observe major age-related ECG changes in C57BL/6N-inbred mice as the differences in the reference ranges of 12-week-old compared to 62-week-old mice were negligible. The generalizability of the C57BL/6N substrain reference ranges was demonstrated by comparison with ECG data from a wide range of non-IMPC studies. The close overlap in data from a wide range of mouse strains suggests that the C57BL/6N-based reference ranges can be used as a robust and comprehensive indicator of normality. We report a unique ECG reference resource of fundamental importance for any experimental study of cardiac function in mice.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Cut of OPEX—Sophisticated Technical Solutions for Hot Strip Mills - Stephan Krämer; Wolfgang Fuchs; Heiko Reichel; Christopher Klein; Angela Ante; Michael Degner (BHM Berg- und Hüttenmännische Monatshefte, 2018)

Serum Response Factor (SRF) Ablation Interferes with Acute Stress-Associated Immediate and Long-Term Coping Mechanisms - Annemarie Zimprich; Gabi Mroz; Christopher Meyer zu Reckendorf; Sofia Anastasiadou; Philip Förstner; Lillian Garrett; Sabine M. Hölter; Lore Becker; Jan Rozman; Cornelia Prehn; Birgit Rathkolb; Kristin Moreth; et al. (Molecular Neurobiology, 2017)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

The developmental impact of prenatal stress, prenatal dexamethasone and postnatal social stress on physiology, behaviour and neuroanatomy of primate offspring: studies in rhesus macaque and common marmoset - Christopher R. Pryce; Yves Aubert; Claudia Maier; Peter C. Pearce; Eberhard Fuchs (Psychopharmacology, 2011)

Flexibility of saccade adaptation in the monkey: different gain states for saccades in the same direction - Shoji Watanabe; Christopher Noto; Albert Fuchs (Experimental Brain Research, 2000)

Flexibility of saccade adaptation in the monkey: different gain states for saccades in the same direction - Shoji Watanabe; Christopher T. Noto; Albert F. Fuchs (Experimental Brain Research, 2000)